1996
DOI: 10.1128/aem.62.8.2773-2777.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Factors on the trans/cis Ratio of Unsaturated Fatty Acids in Pseudomonas putida S12

Abstract: The membrane reactions of Pseudomonas putida S12 to environmental stress were investigated. Cells reacted to the addition of six different heavy metals with an increase in the ratio of trans to cis unsaturated fatty acids. A correlation among the increase in the trans/cis ratio, the toxic effects of the heavy metals, and nonspecific permeabilization of the cytoplasmic membrane, as indicated by an efflux of potassium ions, was measured. Cells previously adapted to toxic concentrations of toluene exhibited incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(57 citation statements)
references
References 50 publications
7
47
1
2
Order By: Relevance
“…The production of trans-UFA in P. putida during growth has been documented Heipieper et al, 1996). However, several studies reported that some P. putida strains produce trans-UFA only in stress or nongrowing conditions, such as during sample preparation (Härtig et al, 2005;Loffhagen et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of trans-UFA in P. putida during growth has been documented Heipieper et al, 1996). However, several studies reported that some P. putida strains produce trans-UFA only in stress or nongrowing conditions, such as during sample preparation (Härtig et al, 2005;Loffhagen et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…P. putida is of particular interest in biotechnology because of its high potential in bioremediation and biodegradation processes (Loh and Cao, 2008;Samuel et al, 2014). Thus, several reports report that trans-UFA plays an important role in the adaptation of diverse P. putida strains to the increase in temperature, the presence of organic solvents and heavy metals, as well as osmotic stress and addition of membrane-active antibiotics (Heipieper et al, 1996;Isken et al, 1997;Neumann et al, 2003). It is generally accepted that cti is constitutively expressed in Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Such a model for the regulation of Cti activity also su⁄ciently explains the often reported relation between the degree of cis^trans isomerization and the toxicity caused by a certain concentration of an environmental stress factor [16,30]. As another result of the reaction catalyzed by the enzyme a reduction of membrane £uidity occurs and, as the enzyme cannot reach its target when membrane £uidity has reached its normal level the enzyme is forced out of the bilayer [45].…”
Section: Regulation Of Ctimentioning
confidence: 98%
“…In summary, all membrane a¡ecting stimuli such as organic solvents, osmotic stress (caused by NaCl and sucrose), heavy metals, heat shock, and membrane-active antibiotics were shown to activate the system [11,30^32]. However, stress conditions, such as osmotic stress caused by glycerol, cold shock, and high pH, that are known not to be activators of cellular K þ -uptake^the ¢rst cellular reaction to membrane damage leading to increased perme-abilization^did not cause activation of Cti [30,31]. Such Concentrations which caused an increase in the trans/cis ratio of unsaturated fatty acids to 50% of the maximum trans/cis level reached at saturating concentrations of the toxin.…”
Section: Physiology and Function Of The Cis^trans Isomerase (Cti) Of mentioning
confidence: 99%
“…The main passive mechanism involves an increase in cell membrane rigidity via alterations in phospholipid composition. Cis/trans-isomerization of unsaturated fatty acids is considered a short-term response, whereas changes in the saturated-to-unsaturated fatty acid ratio are considered a long-term response to solvent exposure (Heipieper and de Bont, 1994;Heipieper et al, 1996;Loffeld and Keweloh, 1996;Junker and Ramos, 1999). The active removal of toxic compounds from the cell membranes to achieve solvent tolerance occurs via mechanisms such as the formation and expulsion of vesicles loaded with toxic compounds that remove the solvents from the cell surface (Kobayashi et al, 2000) and the extrusion of toxic compounds to the external medium in an energy-dependent process mediated by efflux pumps.…”
Section: Introductionmentioning
confidence: 99%